Metal-catalyzed reactions in water - Dixneuf, P. H. (Pierre H.); Cadierno, Victorio, 1969- (Wiley-VCH Verlag & Co. KGaA, 2013)
"This book provides a comprehensive overview of developments in the use of water as a solvent for metal catalysis, illustrating the enormous potential of water in developing new catalytic transformations for fine chemicals synthesis, while reducing environmental impact."--